Eleições para o senado no Paraná: período 1994-2014 - Omar Neto Fernandes Barros; André Nagy (Confins)
Several authors related to Social Sciences have explored the elections issue in Brazil, but the cartographic method is rarely used. Based on cartographic evidence, the work has as objective the analysis of elections results to Senate in the state of Parana 1994 - 2014, to understand the production of spaces by political elections and to propose predictions for 2018. The software used was Philcarto available at http://philcarto.free.fr, it allows beside the maps, assessment and statistic analysis. The main results revealed a preferential regionalization of voting on some candidates which may vary over time.